Crystal structure of porcine pancreatic phospholipase A2 in complex with 2-methoxycyclohexa-2-5-diene-1,4-dione - Dileep, K. V.; Tintu, I.; Mandal, Pradeep K; Karthe, P.; Haridas, M.; Sadasivan, C. (Frontiers in Life Science)
Curcumin possess anti-inflammatory activity. In this study, the binding of curcumin with PLA2 was studied using X-ray crystallography. Since the electron density found at the active site did not match with curcumin, 2-methoxycyclohexa-2-5-diene-1,4-dione (MCW) (the photodegraded product of curcumin) was fitted in the unexplained electron density. To understand the binding mode of actual curcumin, molecular docking study was carried out. The crystallographic and docked structures were superimposed with respect to the ligand position and it was found that curcumin was binding in the hydrophobic cavity of PLA2 with a binding energy of−16.81 Kcal/mol. The binding mode was of such a nature that it prevented the entry of the substrate to the hydrophobic active site. This study indicates that curcumin can act as an inhibitor of PLA2. An animated Interactive 3D Complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:FLS:1.

Structure of d(CCGGGACCGG)4 as a four-way junction at 1.6 Å resolution: New insights into solvent interactions - Chakraborty, Arka; Mandal, Pradeep K; Gautham, Namasivayam (Acta Crystallographica Section F Structural Biology Communications)
The crystal structure of the decamer sequence d(CCGGGACCGG)4 has previously been reported at 2.16 Å resolution as a four-way junction. Here, the structure of this sequence is reported at the significantly higher resolution of 1.6 Å, which is the highest resolution reported for a four-way junction. This allowed the unambiguous identification of an extensive hydration network with distinct patterns and solvent-mediated interactions that shed new light on the role of water in the formation and stabilization of junction structures.

A spatial version of the Itô-Stratonovich correction - Hairer, Martin M; Jan Maas (Annals of Probability)
We consider a class of stochastic PDEs of Burgers type in spatial dimension 1, driven by space–time white noise. Even though it is well known that these equations are well posed, it turns out that if one performs a spatial discretization of the nonlinearity in the “wrong” way, then the sequence of approximate equations does converge to a limit, but this limit exhibits an additional correction term. This correction term is proportional to the local quadratic cross-variation (in space) of the gradient of the conserved quantity with the solution itself. This can be understood as a consequence of the fact that for any fixed time, the law of the solution is locally equivalent to Wiener measure, where space plays the role of time. In this sense, the correction term is similar to the usual Itô–Stratonovich correction term that arises when one considers different temporal discretizations of stochastic ODEs.

Ricci curvature of finite Markov chains via convexity of the entropy - Erbar, Matthias; Jan Maas (Archive for Rational Mechanics and Analysis)
We study a new notion of Ricci curvature that applies to Markov chains on discrete spaces. This notion relies on geodesic convexity of the entropy and is analogous to the one introduced by Lott, Sturm, and Villani for geodesic measure spaces. In order to apply to the discrete setting, the role of the Wasserstein metric is taken over by a different metric, having the property that continuous time Markov chains are gradient flows of the entropy. Using this notion of Ricci curvature we prove discrete analogues of fundamental results by Bakry–Émery and Otto–Villani. Further, we show that Ricci curvature bounds are preserved under tensorisation. As a special case we obtain the sharp Ricci curvature lower bound for the discrete hypercube.

Whitney coverings and the tent spaces T 1,q (γ) for the Gaussian measure - Jan Maas; van Neerven, Jan M; Portal, Pierre (Arkiv för Matematik)
We introduce a technique for handling Whitney decompositions in Gaussian harmonic analysis and apply it to the study of Gaussian analogues of the classical tent spaces T 1,q of Coifman–Meyer–Stein.

Nonadiabatic preparation of spin crystals with ultracold polar molecules - Lemeshko, Mikhail; Krems, Roman; Weimer, Hendrik (Physical Review Letters)
We study the growth dynamics of ordered structures of strongly interacting polar molecules in optical lattices. Using a dipole blockade of microwave excitations, we map the system onto an interacting spin-1/2 model possessing ground states with crystalline order, and describe a way to prepare these states by nonadiabatically driving the transitions between molecular rotational levels. The proposed technique bypasses the need to cross a phase transition and allows for the creation of ordered domains of considerably larger size compared to approaches relying on adiabatic preparation.

Sensitive imaging of electromagnetic fields with paramagnetic polar molecules - Alyabyshev, Sergey V; Mikhail Lemeshko; Krems, Roman V (Physical Review A - Atomic, Molecular, and Optical Physics)
We propose a method for sensitive parallel detection of low-frequency electromagnetic fields based on the fine structure interactions in paramagnetic polar molecules. Compared to the recently implemented scheme employing ultracold 87Rb atoms by Böhi, the technique based on molecules offers a 100-fold higher sensitivity, the possibility to measure both the electric and magnetic field components, and a probe of a wide range of frequencies from the dc limit to the THz regime.

Interaction between polar molecules subject to a far-off-resonant optical field: Entangled dipoles up- or down-holding each other - Mikhail Lemeshko; Friedrich, Břetislav (Molecular Physics)
We show that the electric dipole-dipole interaction between a pair of polar molecules undergoes an all-out transformation when superimposed by a far-off-resonant optical field. The combined interaction potential becomes tunable by variation of wavelength, polarisation and intensity of the optical field and its dependence on the intermolecular separation exhibits a crossover from an inverse-power to an oscillating behaviour. The ability thereby offered to control molecular interactions opens up avenues toward the creation and manipulation of novel phases of ultracold polar gases among whose characteristics is a long-range entanglement of the dipoles' mutual orientation. We devised an accurate analytic model of such optical-field-dressed dipole-dipole interaction potentials, which enables a straightforward access to the optical-field parameters required for the design of intermolecular interactions in the laboratory.

Extensions of MADM (Mosaic Analysis with Double Markers) in Mice - Tasic, Bosiljka; Miyamichi, Kazunari; Simon Hippenmeyer; Dani, Vardhan S.; Zeng, H.; Joo, William; Zong, Hui; Chen-Tsai, Yanru; Luo, Liqun (PLoS One)
Mosaic Analysis with Double Markers (MADM) is a method for generating genetically mosaic mice, in which sibling mutant and wild-type cells are labeled with different fluorescent markers. It is a powerful tool that enables analysis of gene function at the single cell level in vivo. It requires transgenic cassettes to be located between the centromere and the mutation in the gene of interest on the same chromosome. Here we compare procedures for introduction of MADM cassettes into new loci in the mouse genome, and describe new approaches for expanding the utility of MADM. We show that: 1) Targeted homologous recombination outperforms random transgenesis in generation of reliably expressed MADM cassettes, 2) MADM cassettes in new genomic loci need to be validated for biallelic and ubiquitous expression, 3) Recombination between MADM cassettes on different chromosomes can be used to study reciprocal chromosomal deletions/duplications, and 4) MADM can be modified to permit transgene expression by combining it with a binary expression system. The advances described in this study expand current, and enable new and more versatile applications of MADM.

A Nestin-cre transgenic mouse is insufficient for recombination in early embryonic neural progenitors - Liang, Huixuan; Hippenmeyer, Simon; Ghashghaei, H. (Biology open)
Nestin-cre transgenic mice have been widely used to direct recombination to neural stem cells (NSCs) and intermediate neural progenitor cells (NPCs). Here we report that a readily utilized, and the only commercially available, Nestin-cre line is insufficient for directing recombination in early embryonic NSCs and NPCs. Analysis of recombination efficiency in multiple cre-dependent reporters and a genetic mosaic line revealed consistent temporal and spatial patterns of recombination in NSCs and NPCs. For comparison we utilized a knock-in Emx1cre line and found robust recombination in NSCs and NPCs in ventricular and subventricular zones of the cerebral cortices as early as embryonic day 12.5. In addition we found that the rate of Nestin-cre driven recombination only reaches sufficiently high levels in NSCs and NPCs during late embryonic and early postnatal periods. These findings are important when commercially available cre lines are considered for directing recombination to embryonic NSCs and NPCs.

Auto splats: Dynamic point cloud visualization on the GPU - Preiner, Reinhold; Jeschke, Stefan; Wimmer, Michael
Capturing real-world objects with laser-scanning technology has become an everyday task. Recently, the acquisition of dynamic scenes at interactive frame rates has become feasible. A high-quality visualization of the resulting point cloud stream would require a per-frame reconstruction of object surfaces. Unfortunately, reconstruction computations are still too time-consuming to be applied interactively. In this paper we present a local surface reconstruction and visualization technique that provides interactive feedback for reasonably sized point clouds, while achieving high image quality. Our method is performed entirely on the GPU and in screen pace, exploiting the efficiency of the common rasterization pipeline. The approach is very general, as no assumption is made about point connectivity or sampling density. This naturally allows combining the outputs of multiple scanners in a single visualization, which is useful for many virtual and augmented reality applications.

Analytic anti-aliasing of linear functions on polytopes - Thomas Auzinger; Guthe, Michael; Stefan Jeschke
This paper presents an analytic formulation for anti-aliased sampling of 2D polygons and 3D polyhedra. Our framework allows the exact evaluation of the convolution integral with a linear function defined on the polytopes. The filter is a spherically symmetric polynomial of any order, supporting approximations to refined variants such as the Mitchell-Netravali filter family. This enables high-quality rasterization of triangles and tetrahedra with linearly interpolated vertex values to regular and non-regular grids. A closed form solution of the convolution is presented and an efficient implementation on the GPU using DirectX and CUDA C is described.

The propagation approach for computing biochemical reaction networks - Henzinger, Thomas A; Mateescu, Maria (IEEE ACM Transactions on Computational Biology and Bioinformatics)
We introduce propagation models (PMs), a formalism able to express several kinds of equations that describe the behavior of biochemical reaction networks. Furthermore, we introduce the propagation abstract data type (PADT), which separates concerns regarding different numerical algorithms for the transient analysis of biochemical reaction networks from concerns regarding their implementation, thus allowing for portable and efficient solutions. The state of a propagation abstract data type is given by a vector that assigns mass values to a set of nodes, and its (next) operator propagates mass values through this set of nodes. We propose an approximate implementation of the (next) operator, based on threshold abstraction, which propagates only "significant" mass values and thus achieves a compromise between efficiency and accuracy. Finally, we give three use cases for propagation models: the chemical master equation (CME), the reaction rate equation (RRE), and a hybrid method that combines these two equations. These three applications use propagation models in order to propagate probabilities and/or expected values and variances of the model's variables.

Exome sequencing can improve diagnosis and alter patient management - Dixon-Salazar, Tracy J; Silhavy, Jennifer L; Udpa, Nitin; Schroth, Jana; Bielas, Stephanie L; Schaffer, Ashleigh E; Olvera, Jesus; Bafna, Vineet K; Zaki, Maha S; Abdel-Salam, Ghada M; Mansour, Lobna A; Selim, Laila A; et al. (Science Translational Medicine)
The translation of "next-generation" sequencing directly to the clinic is still being assessed but has the potential for genetic diseases to reduce costs, advance accuracy, and point to unsuspected yet treatable conditions. To study its capability in the clinic, we performed whole-exome sequencing in 118 probands with a diagnosis of a pediatric-onset neurodevelopmental disease in which most known causes had been excluded. Twenty-two genes not previously identified as disease-causing were identified in this study (19% of cohort), further establishing exome sequencing as a useful tool for gene discovery. New genes identified included EXOC8 in Joubert syndrome and GFM2 in a patient with microcephaly, simplified gyral pattern, and insulin-dependent diabetes. Exome sequencing uncovered 10 probands (8% of cohort) with mutations in genes known to cause a disease different from the initial diagnosis. Upon further medical evaluation, these mutations were found to account for each proband's disease, leading to a change in diagnosis, some of which led to changes in patient management. Our data provide proof of principle that genomic strategies are useful in clarifying diagnosis in a proportion of patients with neurodevelopmental disorders.

Mutations in BCKD-kinase lead to a potentially treatable form of autism with epilepsy - Gaia Novarino; El-Fishawy, Paul; Kayserili, Hülya; Meguid, Nagwa A; Scott, Eric M; Schroth, Jana; Silhavy, Jennifer L; Kara, Majdi; Khalil, Rehab O; Ben-Omran, Tawfeg I; Ercan-Sencicek, Adife G; Hashish, Adel F; et al. (Science)
Autism spectrum disorders are a genetically heterogeneous constellation of syndromes characterized by impairments in reciprocal social interaction. Available somatic treatments have limited efficacy. We have identified inactivating mutations in the gene BCKDK (Branched Chain Ketoacid Dehydrogenase Kinase) in consanguineous families with autism, epilepsy, and intellectual disability. The encoded protein is responsible for phosphorylation-mediated inactivation of the E1α subunit of branched-chain ketoacid dehydrogenase (BCKDH). Patients with homozygous BCKDK mutations display reductions in BCKDK messenger RNA and protein, E1α phosphorylation, and plasma branched-chain amino acids. Bckdk knockout mice show abnormal brain amino acid profiles and neurobehavioral deficits that respond to dietary supplementation. Thus, autism presenting with intellectual disability and epilepsy caused by BCKDK mutations represents a potentially treatable syndrome.

Ground state properties of multi-polaron systems - Frank, Rupert L; Lieb, Élliott H; Robert Seiringer; Thomas, Lawrence E
We summarize our recent results on the ground state energy of multi-polaron systems. In particular, we discuss stability and existence of the thermodynamic limit, and we discuss the absence of binding in the case of large Coulomb repulsion and the corresponding binding-unbinding transition. We also consider the Pekar-Tomasevich approximation to the ground state energy and we study radial symmetry of the ground state density.

Microscopic derivation of the Ginzburg-Landau model - Frank, Rupert L; Hainzl, Christian; Robert Seiringer; Solovej, Jan P
We present a summary of our recent rigorous derivation of the celebrated Ginzburg-Landau (GL) theory, starting from the microscopic Bardeen-Cooper-Schrieffer (BCS) model. Close to the critical temperature, GL arises as an effective theory on the macroscopic scale. The relevant scaling limit is semiclassical in nature, and semiclassical analysis, with minimal regularity assumptions, plays an important part in our proof.

Absence of bound states implies non-negativity of the scattering length - Seiringer, Robert (Journal of Spectral Theory)
We show that bosons interacting via pair potentials with negative scattering length form bound states for a suitable number of particles. In other words, the absence of many-particle bound states of any kind implies the non-negativity of the scattering length of the interaction potential.

On Manin's conjecture for a family of Châtelet surfaces - de la Bretèche, Régis; Timothy Browning; Peyre, Emmanuel (Annals of Mathematics)
The Manin conjecture is established for Châtelet surfaces over Q aris-ing as minimal proper smooth models of the surface Y 2 + Z 2 = f(X) in A 3 Q, where f ∈ Z[X] is a totally reducible polynomial of degree 3 without repeated roots. These surfaces do not satisfy weak approximation.

Inhomogeneous quadratic congruences - Baier, Stephan; Timothy Browning (Functiones et Approximatio, Commentarii Mathematici)
For given positive integers a, b, q we investigate the density of solutions (x, y) ∈ Z2 to congruences ax + by2 ≡ 0 mod q.